KEKUATAN PEMBUKTIAN SURAT KETERANGAN GANTI RUGI (SKGR) BERDASARKAN PERKARA PERDATA NOMOR 56/PDT/G/2009/PN.PBR - Mentari Maharani Br Ginting; Maryati Bachtiar; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Land is a right which can not be separated from human needs. Need of land will be increasing in line with the increase in population, the number of business, and other needs related to the land. Land can be lawful if it has a certificate as proof of ownership of the land. It is quite important given the current set is a lot happening in the field of land registration issues especially those concerning land ownership papers. Issues to be discussed is the first, of how the strength of evidence a certificate of indemnity (SKGR) based on a civil case number 56 / PDT / G / 2009 / PN.PBR, and secondly whether consideration of the judge in deciding a civil case number 56 / PDT / G / 2009 / PN.PBR meets the origin of justice.The research method used a normative legal research. Data source of this research is secondary data, with data collection techniques using literature study. This study the authors use qualitative analysis, data were analyzed by not using statistic or math or another math statistics, but simply descriptive outline of the data that has been obtained by inference method.The results of this study can be concluded that the strength of evidence possessed by SKGR as a letter under the land. Basic consideration of the judge in deciding a civil case number 56 / PDT / G / 2009 / PN.PBR not meet the principle of justice because of the lawsuit clearly lacks the parties, object of the case are not clear or fuzzy, and the judge did not consider the issuance of certificates of land that has been through administration right or not so the judge ruled in favor of the party who has SKGR land than the land certificate. This study suggests to people who already have SKGR forward into the land certificate and judge should consider the rights of the parties so that there are no losers, especially in terms of land registration activities.Keywords: Verification – SKGR - Justice Ground – Judge Konsideration